The Role Of Attar’s Metaphor In Science And Technology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Metaphor is a literary technique where one thing is compared to another by stating they share the same qualities. Metaphors are powerful tools that allow us unleash our creativity, expose our inner words, and stand out our writing and speech.  In futures studies, metaphors are employed to assist us comprehend the key elements of the future and gain insight into its intricacies. In particular, metaphors aim to provide a simplified explanation of the relationship between various concepts and phenomena. Approximately 2000 years ago, Aristotle was among the first writers to employ metaphors in a scientific setting. Metaphor is "a conceptual system that allows us to understand and experience one type of thing in terms of another," according to Miller. (2006). Metaphor is "a cross-domain mapping between the source (secondary) and the target (primary) domains," according to Hellsten (2002). Using an all-encompassing, abstract approach, this mapping method uses some, but not all, of the source's features to highlight some of the target's features.